2006
DOI: 10.1182/blood-2006-03-008706
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the intensity of the pretransplantation conditioning regimen in patients with prior invasive aspergillosis undergoing allogeneic hematopoietic stem cell transplantation: a retrospective survey of the Infectious Diseases Working Party of the European Group for Blood and Marrow Transplantation

Abstract: In this retrospective study, we analyzed the outcomes of 129 patients who underwent an allogeneic hematopoietic stem cell transplantation (allo-HSCT) and had a history of probable or proven invasive aspergillosis (IA), of whom 57 (44%) received a reduced-intensity conditioning (RIC). Overall, 27 patients with IA progressed after the allo-HSCT (cumulative incidence [CumInc] at 2 years, 22%). The variables that increased the 2-year CumInc of IA progression were (1) longer duration of neutropenia after transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 35 publications
3
75
1
3
Order By: Relevance
“…Earlier studies reported that residual radiological abnormalities before transplantation were a major risk factor for the failure of IFI prophylaxis, [4][5][6]16 which was confirmed by our study. A total of 24 cases (49.0%) in our study had residual disease before transplantation and we assessed the outcome of the preceding IFI in this subgroup.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Earlier studies reported that residual radiological abnormalities before transplantation were a major risk factor for the failure of IFI prophylaxis, [4][5][6]16 which was confirmed by our study. A total of 24 cases (49.0%) in our study had residual disease before transplantation and we assessed the outcome of the preceding IFI in this subgroup.…”
Section: Discussionsupporting
confidence: 80%
“…No significant difference was found between the two groups regarding distribution of risk factors. The results indicate that Allo-HSCT is feasible for patients with a history of IFI and a favorable outcome can be achieved with powerful prophylaxis 4,6,16 (Figure 2).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations